Judd-Ofelt and quantum cutting analysis of Eu3+ or Pr3+ doped β-NaGdF4 nanorods obtained by rapid coprecipitation method. (May 2020) - Cheroura, Y.; Smara, Z.; Potdevin, A.; Boyer, D.; Chafa, A.; Ziane, O.; Mahiou, R.
Graphical abstract: Highlights: β-NaGdF4 :Ln 3+ (Ln = Eu or Pr) nanorods have been synthesized by coprecipitation at low temperature for the first time. Quantum cutting process between Gd 3+ and Eu 3+ and on Pr 3+ was evidenced under near VUV excitation. Spectroscopic properties have been investigated and discussed on the basis of the Judd-Ofelt theory. Abstract: Pure hexagonal β-NaGdF4 and Eu 3+ or Pr 3+ -doped β-NaGdF4 nanocrystals in shape of nanorods of ∼140 nm of length have been synthesized using a simple and rapid coprecipitation method. XRD analysis evidenced pure single phases exhibiting characteristic luminescence of Eu 3+ or Pr 3+ ions when excited under UV or blue radiations. Samples gave rise to intense orange-red emission and quite white emission in the case of respectively Eu 3+ or Pr 3+ doped samples. Optical properties are discussed in the frame of Judd-Ofelt theory and considering that an energy transfer occurs between active ions. Notably it was found that the quantum-cutting by a two-step energy transfer from Gd 3+ to Eu 3+ can improve the red emission of Eu 3+ ions under near-VUV excitation. Such quantum-cutting mechanism has been also considered in the case of Pr 3+ doped β-NaGdF4 . However, the efficiency of both processes in comparison with literature suggest that only one part of the energy in the excited states within Gd 3+ can be transferred to Eu 3+ for its red emission. In the case of Pr 3+ ions, the energy is more probably released through the self-trapped exciton emission certainly due to the lack of resonant VUV excitation.